Masters of Caricature : from Hogarth and Gillray to Scarfe and Levine - Feaver, William (New York : Alfred A. Knopf, 1981)
Ghezzi, Pier Leone ; Boyle, Dorothy ; Goupy, Joseph ; Patch, Thomas ; Hogarth, William ; Townshend, George ; Darly, Matthew ; Foulquier, François Joseph ; Hurd, Nathaniel ; Grimm, Samuel Hieronymus ; Rowlandson, Thomas ; Chodowiecki, Daniel ; Bunbury, Henry ; Grose, Francis ; Woodward, George Murgatroyd ; Collings, Samuel ; Lawrence, Thomas ; Gillray, James ; Sayers, James ; Dent, William ; Kay, John ; Cruikshank, Isaac ; Dighton, Robert ; Schadow, Johann Gottfried ; Atkin, James ; Williams, Charles ; Cruikshank, George ; Elmes, William ; Voltz, Johann Michael ; Boilly, Louis Léopold ; Marks, J. Lewis ; Heath, William ; Landseer, Edwin Henry ; Dighton, Richard ; Doyle, John ; Robinson, Henry R. ; Philipon, Charles ; Dantan, Jean-Pierre Edouard ; Villers, Charles-Joseph Traviès des ; Johnston, David Claypool ; Roubaud, Benjamin ; Daumier, Honoré ; Carjat, Etienne ; Leech, John ; Thackeray, William Makepeace ; Grandville, Jean-Ignace-Isidore Gérard ; Braun, Caspar ; Tournachon, Gaspard Félix ; Bellew, Frank Henry Temple ; Monet, Claude ; Volck, Adalbert John ; Scholz, Wilhelm ; Busch, Wilhelm ; Tenniel, John ; Labadie, Georges ; de Noé, Amédée ; Betbeder, Faustin ; Doré, Gustave ; Gaillard, A.A. ; Petit, Alfred Le ; Bryan, Alfred ; Régamey, Félix Elie ; Levy, Alphonse Jacques ; Evrard, Emile ; de Guines, Louis-Alexandre Gosset ; Colomb, Alphonse Hector ; Nast, Thomas ; Bengough, John Wilson ; Keppler, Joseph ; Hopkins, Livingstone ; Wales, James Albert ; Waddy, Frederick ; Cecioni, Adriano ; Jacques, James Joseph ; Pellegrini, Carlo ; Furniss, Harry ; de Paleologu, Jean ; Ward, Leslie ; Sambounre, Edward Linley ; Gillam, Bernhard ; Baxter, William Giles ; Racey, Arthur George ; Gould, Francis Carruthers ; Zimmerman, Eugene ; Julien, Henri ; etc.
Biografie
boek